2018
DOI: 10.1159/000489700
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic-Reperfusion Injury Increases Matrix Metalloproteinases and Tissue Metalloproteinase Inhibitors in Fetal Sheep Brain

Abstract: Hypoxic-ischemic brain injury is a leading cause of neurodevelopmental morbidities in preterm and full-term infants. Blood-brain barrier dysfunction represents an important component of perinatal hypoxic-ischemic brain injury. The extracellular matrix (ECM) is a vital component of the blood-brain barrier. Matrix metalloproteinases (MMPs) and tissue inhibitors of matrix metalloproteinases (TIMPs) are important ECM components. They contribute to brain development, blood-brain barrier maintenance, and to regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…As already cited above, reperfusion after ischemia triggers a particular set of potential damaging mechanisms, and an eventful one is the activation of matrix metalloproteinases (MMP), a class that comprises, among others, gelatinases (MMP-2 and -9) and collagenases (MMP-8 and -13) [385]. MMPs are important regulators of several metabolic mechanisms such as the extracellular matrix remodeling, and also regulate immune responses [386], blood–brain barrier maintenance, and regenerative and structural repairing after IRI in the brain [385]. However, in the pathological context of I/R, MMPs may promote the degradation of intracellular proteins and lead to structural and functional impairment, as we previously stated in this review.…”
Section: Therapeutics: the Pharmacological Approachmentioning
confidence: 99%
“…As already cited above, reperfusion after ischemia triggers a particular set of potential damaging mechanisms, and an eventful one is the activation of matrix metalloproteinases (MMP), a class that comprises, among others, gelatinases (MMP-2 and -9) and collagenases (MMP-8 and -13) [385]. MMPs are important regulators of several metabolic mechanisms such as the extracellular matrix remodeling, and also regulate immune responses [386], blood–brain barrier maintenance, and regenerative and structural repairing after IRI in the brain [385]. However, in the pathological context of I/R, MMPs may promote the degradation of intracellular proteins and lead to structural and functional impairment, as we previously stated in this review.…”
Section: Therapeutics: the Pharmacological Approachmentioning
confidence: 99%
“…Thrombolytic therapy and mechanical recanalization are effective methods for blood re-supply after ischemia. However, for some specific patients, the injury induced by ischemia can be aggravated by ischemic/reperfusion, which is termed as “brain ischemic/reperfusion injury” [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“… 41 Although research on MMP-13 in liver IR injury is not available, a study suggested that MMP-13 is important in IR-related brain injury, and the level of MMP-13 gradually increased with time after cerebral IR and was markedly higher than that in the sham group after 48 hours. 42 CCL3 and CCL4, also known as macrophage inflammatory protein-1α (MIP-1α) and macrophage inflammatory protein-1β (MIP-1β), were examined in liver endothelial cells several hours after liver transplantation reperfusion, and they were continuously expressed during acute cellular rejection. It seemed that inhibition of the secretion of these chemokines was one of the mechanisms of the success of corticosteroid therapy for acute rejection.…”
Section: Discussionmentioning
confidence: 99%